Vision tests of sensory judges - review - Sipos, László; Nyitrai, Ákos; Szabó, Dániel; Urbin, Ágnes; Nagy, Balázs Vince (Élelmiszervizsgálati Közlemények, 2020)
In sensory examinations, judges must be in good general health. They should not have any deficiencies that could affect their perception or adversely affect their sensory performance, and thus can affect the reliability of their judgments. The vision of a judge is basically determined by three factors: visual acuity, contrast sensitivity and color vision. In the international practice of sensory analyses, color vision is generally examined. Color blindness is typically tested using the Ishihara pseudo-isochromatic color test, while color discrimination ability is examined using the Farnsworth-Munsell 100 hue test [1]. The most accurate tool to detect color blind people is the anomaloscope. Screening for color blind people is important because they have both poorer color discrimination abilities and poorer color identification abilities. The results of online color vision tests are significantly affected by the display device and its settings (monitor resolution, color-correct calibration), as well as test conditions: test geometry (relative position of the light source, the test book and the eye), photometric and spectral nature of the light source and the monitor, and the adaptation state of the eye. Unfortunately, the specifications for standard sensory tests do not require the visual acuity and contrast sensitivity testing of sensory judges, however, these properties obviously affect visual perception, so testing them is necessary.